Factors of Psychological Preparations for War Tragedy - Kron, Leposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
In this paper, the author has discussed psychological theories of violent behaviour, which aspire to explain the origin and structure of human aggressiveness, different rates of extreme violence in different types of populations, and, finally, the role of psychological factors in the genesis of major and bloody conflicts between human communities, peoples and states.